COVID-19 Disease Severity and Blood Test Results in Unvaccinated and Vaccinated Patients at Bhayangkara Hospital, Denpasar, Indonesia - Muyasaroh, Chanif Lutfiyati; Wiratmini, Ngurah Intan; Sukmaningsih, Anak Agung Sagung Alit (Folia Medica Indonesiana, 2023)
Highlights: This original research report on the differences in disease severity and blood test results between unvaccinated and vaccinated COVID-19 patients is quite novel, as the COVID-19 pandemic was still happening when this study was carried out. This original research report offers information on the advantages of the COVID-19 vaccines and provides data that the public may use as scientific evidence to counter hoaxes. Abstract The COVID-19 pandemic caused by SARS-CoV-2 is an unprecedented event in human history. Vaccines are a safe, long-term solution for addressing the COVID-19 pandemic. This study aimed to investigate the differences in disease severity and blood test results between unvaccinated and vaccinated COVID-19 patients. This study used an analytical observational method with purposive sampling. A total of 90 COVID-19 patients at Bhayangkara Hospital, Denpasar, Indonesia, were divided into three groups: unvaccinated group (V0), two-dose vaccinated group (Vp), and three-dose vaccinated group (Vb). Primary data were collected from July to December 2022, while secondary data were collected from January 2021 to June 2022. The data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test, as well as one-way ANOVA test followed by Tukey's honestly significant difference (HSD) test with a confidence interval (CI) of 95% and α of 5%. The results revealed significant differences in disease severity (p<0.001). V0 had a higher percentage of severe (36.7%) and critical (6.7%) symptoms than Vp (severe=10.0%; critical, n=0) and Vb (severe and critical, n=0). The follow-up tests revealed significant differences in disease severity between V0 and Vp (p<0.001), V0 and Vb (p<0.001), as well as Vp and Vb (p=0.001). Blood test results revealed significant differences in lymphocytes (p=0.005), monocytes (p<0.001), monocyte-to-lymphocyte ratio (MLR) (p<0.001), and eosinophils (p=0.037). The follow-up tests revealed significant differences in these four indicators between V0 and Vb, in all parameters except for lymphocytes between V0 and Vp, and in lymphocytes only between Vp vs Vb. In conclusion, unvaccinated patients had a higher percentage of severe and critical symptoms than vaccinated patients. The blood test results revealed significant differences in lymphocytes, monocytes, MLR, and eosinophils. Unvaccinated patients had lower lymphocyte counts, higher MLR levels, and higher monocyte counts than vaccinated patients.